Penanggulangan Bencana sebagai Soft Power dalam Diplomasi Indonesia - Herningtyas, Ratih (Jurnal Hubungan Internasional, 2014)
This paper aims to describe how the issue of disasters in Indonesia can be modified into a positive social capital to solve social, economic, political and social cultureâs problems in disaster prone areas. This paper found that Indonesiaâs disaster managements get worldwide recognition and increases Indonesiaâs competitiveness toward other countries. These recognitions become the sources of Indonesiaâs soft power, and can be used as a strategic instrument to build regional cooperation and international collaboration to improve infrastructure that can reduce the degree of disastersâ material and immaterial losses.